The effects of a US-China trade war on Sub-Saharan Africa: Pro-active domestic policies make the difference - ARI, ALİ (My University, 2023)
This study simulates the impact of the change in trade policy between the US and China on the trade volume and economic prosperity of Sub-Saharan Africa (SSA). To do that, we employ a Computable General Equilibrium (CGE) model based on the Global Trade Analysis Project (GTAP) with different scenarios focusing on increases in tariffs. The results show that the tariff increases negatively affect the US and China in terms of trade volume and economic growth, while it leads to trade diversion and creation for the SSA. This offers valuable opportunities in improving exports and economic growth, particularly for Ethiopia, Kenya, and Nigeria. On the sectorial level, the findings imply that agriculture, food, and oil and gas sectors are positively affected in terms of export volume, while mineral, metal and service sectors are negatively impacted by the trade war.
Keywords: Sosyal ve Beşeri Bilimler; İktisat; Social Sciences and Humanities; Economics; Sosyal Bilimler (SOC); Ekonomi ve İş; EKONOMİ; Social Sciences (SOC); ECONOMICS & BUSINESS; ECONOMICS; Ekonomi ve Ekonometri; Sosyal Bilimler ve Beşeri Bilimler; Economics and Econometrics; Social Sciences & Humanities; CGE; GTAP; Sub-Saharan Africa; Trade policy; Trade war; CGE; GTAP; Sub-Saharan Africa; Trade policy; Trade war